Social workers' compensation models and the Czech statutory employer liability insurance - Jaroslav Vostatek (DANUBE: Law, Economics and Social Issues Review, 2020)
Czech workers' compensation is "exemplified" by the adoption of the Worker's Accident Insurance Act in 2006, four deferments of its effective date and then complete annulment of the Act. A temporary settlement aimed at resolving the incompatibility of the communist model of workers' compensation for work accidents and occupational illnesses with the transition to a market economy after 1989 involved the implementation of statutory employer liability insurance for work accidents and occupational illnesses, outsourced to two private insurance companies; the current Czech government does not seem to have a know how to deal with it. The objective of this paper is primarily to advise the government using primarily the formulation and comparison of four basic social workers' compensation models and furthermore considering the existing sickness, pension and health insurance systems. The choice of a social model is namely a matter of public choice, but intensive lobbying also constitutes part of these processes. The analyses result in a recommendation to "dissolve" the statutory employer liability insurance into a jointly collected social insurance contribution for sickness and pension insurance, and partly to transform the current accident benefits into increased sickness and pension benefit assessments and partly to cancel them.
Keywords: 330; Workers' Compensation; Welfare Regimes; Social Accident Insurance; Czech Social Reforms; Beveridge; Bismarck